National Innovation System (NIS) as a Means for Development: Policies, Opportunities, and Challenges in Ethiopia. [version 2; peer review: 2 approved, 1 approved with reservations] - Ashenafi Bayinesagn; Filimon Hando; Tegegn Belay; Kassahun Sube (F1000Research)
Introduction A robust National Innovation System (NIS) has become crucial for fostering socioeconomic progress and competitiveness in emerging economies like Ethiopia, and its success relies significantly on successful implementation of science, technology, and innovation (STI) policies. Methods Using a document review approach, the study examined at various STI policies and legal frameworks regarding their relation to the National Innovation System (NIS). Results The results of the study indicate that the National Innovation System is supported by the current STI policies and legal fremeworks. There is evidence that an enabling environment emerges to strengthen the NIS, which includes enhancing R&D funding, improving university-industry linkage, and promoting an entrepreneurial culture. Similar to this, research shows that Ethiopia has a lot of potential to increase STI’s capacity because of its advantageous location, wealth of natural resources, and expanding support from the public and private sectors. The execution of STI laws and policies is nevertheless hampered by a number of issues, such as poor R&D investment, weak university-industry linkage, poor coordination among stakeholders, and inadequate infrastructure. Conclusion Ethiopia’s STI policies and legal frameworks are essential for driving economic growth, innovation, and competitiveness by fostering an environment that encourages collaboration and technology transfer. Nevertheless, the country faces challenges in effectively implementing these comprehensive policies due to existing barriers like policy gaps and insufficient institutional support. To strengthen its National Innovation System and promote sustainable economic development, Ethiopia must assess current opportunities, address these obstacles, and explore alternative policies that can enhance its STI capabilities.